2010
DOI: 10.1016/j.febslet.2010.02.016
|View full text |Cite
|
Sign up to set email alerts
|

PINK1 is recruited to mitochondria with parkin and associates with LC3 in mitophagy

Abstract: Edited by Jesus AvilaKeywords: PTEN-induced putative kinase 1 Parkin Mitophagy Autophagy Parkinson's disease a b s t r a c t Mutations in PTEN-induced putative kinase 1 (PINK1) cause recessive form of Parkinson's disease (PD). PINK1 acts upstream of parkin, regulating mitochondrial integrity and functions. Here, we show that PINK1 in combination with parkin results in the perinuclear mitochondrial aggregation followed by their elimination. This elimination is reduced in cells expressing PINK1 mutants with wild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
180
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 222 publications
(186 citation statements)
references
References 20 publications
2
180
2
2
Order By: Relevance
“…Later studies have supported Narendra's findings showing that PINK1 acts upstream from Parkin, and that both proteins are recruited to depolarized mitochondria (Kim et al, 2008;Kawajiri et al, 2010;Matsuda et al, 2010;Vives-Bauza et al, 2010). The DJ-1 protein, already known by its antioxidant, chaperone-like and transcriptional modulator functions, has been recently proposed to act in parallel with PINK1 and…”
Section: Linking Oxidative Stress and Mitochondrial Dynamics In Pd Amentioning
confidence: 72%
“…Later studies have supported Narendra's findings showing that PINK1 acts upstream from Parkin, and that both proteins are recruited to depolarized mitochondria (Kim et al, 2008;Kawajiri et al, 2010;Matsuda et al, 2010;Vives-Bauza et al, 2010). The DJ-1 protein, already known by its antioxidant, chaperone-like and transcriptional modulator functions, has been recently proposed to act in parallel with PINK1 and…”
Section: Linking Oxidative Stress and Mitochondrial Dynamics In Pd Amentioning
confidence: 72%
“…As outlined above, many studies in the field of mitophagy involve a determination of colocalization between mitochondrial labels and markers for autophagy (for example MAP1LC3 19,21,23,29,30 ) or other salient proteins such as PARK2 30,31 or PINK1 30 The recruitment of mitochondria has also been analyzed through colocalization of other autophagy markers such as Atg8 or GABARAPL1 with Atg32 26,27 or BNIP3L, 15 respectively. Quantification of the extent to which markers colocalize provides a numerical index that can be subjected to statistical analysis.…”
Section: Image Analysis and Quantification Of Mitophagymentioning
confidence: 99%
“…The second family are the GABA A receptor-associated proteins (GABARAP) which has four members: the first is GABARAP, the second member is GABARAPL1 (GABA(A) receptor-associated protein like 1)/ATG8L/GEC1, the third member is GABARAPL2 (GABA(A) receptor-associated protein like 2)/GATE-16/GEF2, with the final member GABARAPL3 (GABA(A) receptor-associated protein like 3). 28 Examples where mitochondria have been labeled along with MAP1LC3 as either a fluorescent protein (FP) chimera 19,21,23,29 or by using antibodies raised against MAP1LC3 30 are noted. MAP1LC3 reporters can also be combined with many other mitochondrial/mitophagy fluorescent markers, including TMRM, 21 mitochondrial-targeted RFP, 19 PARK2 as an FP chimera, 30,31 PINK1 (Flag epitope-tagged PINK1), 30 and MitoTracker ® dyes.…”
Section: Monitoring Mitophagy Through Colocalization Of Mitochondrialmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we observed Parkin aggregation in the neural cells of embryos from diabetic dams, suggesting that an impaired Parkin-mediated UPS may be involved in diabetic embryopathy. PARKIN interacts with PTEN-induced putative kinase 1 (PINK1) on the mitochondrial membrane (48,49). The action of the PARKIN-PINK1 complex is to regulate mitochondrial morphogenesis and remove damaged mitochondria through a form of ALS (50,51).…”
Section: Discussionmentioning
confidence: 99%